INTEGRASI HUKUM DAN ETIKA DIGITAL: KONTROL SOSIAL TERHADAP PERILAKU NETIZEN DI MEDIA SOSIAL - Nabila Fitri Gunawan; Nabila Inita Zahra; Silfia Hanani (Jurnal Salome : Multidisipliner Keilmuan, 2025)
In the increasingly developing digital era, social media has become the main space for interaction and dissemination of information. However, freedom of expression in cyberspace is often misused, leading to unethical behavior such as the spread of hoaxes, hate speech, and violations of privacy. This phenomenon shows the urgency of integration between law and digital ethics as a mechanism of social control over netizen behavior. This study aims to analyze the role of law and digital ethics in regulating interactions on social media, as well as the challenges in its implementation. The method used is a literature study by reviewing various literature related to digital law and ethics, including the Electronic Information and Transactions Law (UU ITE). The results of the study show that the application of laws such as the ITE Law plays an important role in imposing sanctions on violations, while digital ethics functions as a moral guideline that shapes netizens' awareness in communicating responsibly. However, challenges such as low digital literacy, multiple interpretations of law, and anonymity in cyberspace are still obstacles in the implementation of social control. Therefore, a collaborative approach is needed between the government, social media platforms, academics, and the community to improve legal literacy and digital ethics. Broad education and consistent law enforcement can create a healthier, safer, and more ethical social media ecosystem. Thus, the integration of digital law and ethics can be an effective solution in controlling netizen behavior in order to create a more positive and harmonious digital space.